PENINGKATAN PENGETAHUAN SISWA MELALUI PENGGUNAAN MEDIA POSTER BERBANTUAN VIDEO PEMBELAJARAN MATERI "AKU CINTA PANCASILA" KELAS I SDN KALIBANTENG KIDUL 01 - Ro'ikhatul Jannah; Wina Auliya Fadhilah; Susilo Tri Widodo; Nur Indah Wahyuni; Rus Yuliarti (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2023)
This research aims to determine the role of teachers in developing creative and innovative learning media in Pancasila education learning to overcome the problem of learning difficulties in students. This research was carried out at SDN Kalibanteng Kidul 01 class IB with a population of 29 students. This type of research method is descriptive qualitative. Data collection techniques include: observation, interviews, and documentation. The research results obtained from observation data sources through direct interviews with class IB teachers show that the problem faced by students in learning Pancasila education is that students are not able to understand the sound and meaning of Pancasila and memorize the color components contained in Pancasila. symbols, and lack of use of learning media. who are creative and innovative. The solution used by researchers to overcome this problem was to carry out 2 cycles of classroom action to determine the increase in students' knowledge through the use of poster media assisted by the video learning material "I Love Pancasila".